ChemInform Abstract: Novel Red‐Emitting Garnet Na2CaTi2Ge3O12:Pr 3+, Na+ Phosphors. Issue 26 (1st July 2014) - Huang, Chien‐Hao; Luo, Liyang; Yeh, Yao‐Tsung; Jang, Shyue‐Ming; Liu, Wei‐Ren
Abstract A series of red‐emitting garnet Na2CaTi2Ge3O12:Pr 3+, Na+ phosphors are prepared by solid state reaction of stoichiometric mixtures of NaCO3, CaCO3, TiO2, GeO2, and Pr2O3 (alumina crucible, 950 °C, 8 h, reducing atmosphere).